Senescence and Apoptosis During in vitro Embryo Development in a Bovine Model - Ramos-Ibeas, Priscila; Gimeno, Isabel; Cañón-Beltrán, Karina; Gutiérrez-Adán, Alfonso; Rizos, Dimitrios; Gómez, Enrique (Frontiers in Cell and Developmental Biology, 2020)
According to the World Health Organization, infertility affects up to 14% of couples under reproductive age, leading to an exponential rise in the use of assisted reproduction as a route for conceiving a baby. In the same way, thousands of embryos are produced in cattle and other farm animals annually, leading to increased numbers of individuals born. All reproductive manipulations entail deviations of natural phenotypes and genotypes, with in vitro embryo technologies perhaps showing the biggest effects, although these alterations are still emerging. Most of these indications have been provided by animal models, in particular the bovine species, due to its similarities to human early embryo development. Oocytes and embryos are highly sensitive to environmental stress in vivo and in vitro. Thus, during in vitro culture, a number of stressful conditions affect embryonic quality and viability, inducing subfertility and/or long-term consequences that may reach the offspring. A high proportion of the embryos produced in vitro are arrested at a species-specific stage of development during the first cell divisions. These arrested embryos do not show signs of programmed cell death during early cleavage stages. Instead, defective in vitro produced embryos would enter a permanent cell cycle arrest compatible with cellular senescence, in which they show active metabolism and high reactive oxygen species levels. Later in development, mainly during the morula and blastocyst stages, apoptosis would mediatethe elimination of certain cells, accomplishing both a physiological role in to balancing cell proliferation and death, and a pathological role preventing the transmission of damaged cells with an altered genome. The latter would acquire relevant importance in in vitro produced embryos that are submitted to stressful environmental stimuli. In this article, we review the mechanisms mediating apoptosis and senescence during early embryo development, with a focus on in vitro produced bovine embryos. Additionally, we shed light on the protective role of senescence and apoptosis to ensure that unhealthy cells and early embryos do not progress in development, avoiding long-term detrimental effects.